Caregiving during the Time of COVID‐19: A Multi‐State Qualitative Study of Family Caregiver Experiences and Decision‐Making. (15th September 2021) - Sadler, Tonie; Yan, Kevin; Pollack, Harold; Brauner, Daniel; Konetzka, R. Tamara
Abstract : Research Objective: COVID‐19 poses unique challenges to family caregivers. This study explores how family caregivers for older adults with cognitive impairments experience and make decisions about caregiving during a global pandemic. Study Design: Using purposive sampling, family caregivers participated in open‐ended qualitive interviews (2019–2020), until thematic saturation was reached. Questions broadly examined caregivers' experiences and decisions, focusing on decisions made around type of care setting. Questions about responses to the Pandemic were added as events unfolded. States were selected to represent variation in Home and Community Based Service (HCBS) expenditures as a percentage of total Medicaid long‐term services and support expenditures. They include; Arkansas, Florida, Illinois, Minnesota, New York, North Carolina, and Oregon. All participants were actively involved in the care of someone with dementia or another cognitive impairment over the age of 60. Population Studied: 63 family caregivers were interviewed across eight states. About 89% of participants were female, 78% white, 10% black, 5% Asian, 3% biracial, 2% Native American. 36% of respondents reported that those they care for receive Medicaid. Principal Findings: This analysis focused on several COVID‐related caregiver decisions: changes in care, challenges with care utilization and access, and policies or changes in care that were helpful during the pandemic were of focus. Four key themes emerged. First, family caregivers experienced communication challenges with long term care facilities often due to COVID‐19 restriction policies. They reported an inability to asses care quality, participate in medical appointments, or communicate with their loved ones. Second, some families chose to cease the care supports they were receiving. Participants cited concern about the virus itself, and about indirect pandemic effects such as their loved ones experiencing confusion, loneliness, and poor care. Third, many respondents expressed the desire to avoid future nursing care, and expressed hesitancy towards seeking HCBS until the pandemic is curbed. Finally, many caregivers reported that telemedicine and other remote health care interventions improved their workload and service access. Conclusions: We examined how the pandemic has impacted decision‐making among caregivers of older adults with cognitive impairments. Family caregivers experienced significant concern about COVID‐19 itself, and about the indirect consequences of caregiving caused by the pandemic. Caregivers have also shown flexibility and adaptability in ceasing selected services, contingently continuing services, and utilizing telemedicine and other remote healthcare interventions to protect their loved ones. Many family caregivers utilized remote health care interventions such telemedicine, no‐contact prescription and grocery delivery. Such measures improved service access and reduced caregiver workload. Implications for Policy or Practice: Given the persistent challenges posed by COVID‐19, long term service organizations have an opportunity to enhance their policies to meet the needs of caregivers and those they care for. First, there is a need to expand and continue telemedicine and other remote healthcare interventions, while adapting these technologies to the needs of families. Second, bolstering communication supports when on lock down in nursing facilities may reduce confusion and feelings of isolation. Finally, procedures are needed for safe and trusted pathways to utilize HCBS and nursing care during a pandemic including sufficient PPE, increased staffing, and utilization of evidence‐based protocols. Primary Funding Source: National Institutes of Health.